NILAI TAUHID DALAM TRADISI JEGURAN: PENDEKATAN KULTURAL DI KOLAM PESAREAN MBAH MUTAMAKKIN, KAJEN- PATI - Siti Muafanah; Widayat Mintarsih; Ema Hidayanti (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
The jeguran tradition is one of the cultural practices of the Javanese community in the pesarean pond of Kajen Village, Pati Regency. Although wrapped in local traditions, there are Islamic values ​​in it, especially the value of monotheism. This study aims to reveal the meaning and values ​​of monotheism contained in the jeguran tradition and explain how the jeguran tradition becomes a means of conveying Islamic teachings to the community with a cultural approach. The method used is qualitative with a case study approach. Data were obtained through observation, in-depth interviews with community leaders, and participants in the jeguran activities. The results of the study show that the jeguran tradition contains monotheism values ​​that are reflected as a form of the oneness of Allah through prayer and intentions that are said, influencing a person's life, physical and spiritual cleansing, an attitude of surrender and trusting completely to Allah. This tradition is an effective cultural da'wah media in spreading the teachings of monotheism in a society that is still strong with Javanese cultural values ​​so that local traditions can be a strategic media in conveying Islamic values, especially monotheism without eliminating local wisdom.